Síntese de carbono ativado magnético a partir de sementes de maracujá e sua aplicação na adsorção de corante azul de metileno - Vieira, Bruno Rafael Del Rio (2021)
The passion fruit industry has been growing over the years in Brazil, with this growth the generation of waste has also extended, the seeds and the passion fruit peel do not haven’t appropriate destinations, as a way to add value to the waste, the seed can be synthesized to become activated carbon, in addition, it is possible to produce materials with magnetic properties. Once transformed into activated carbon this waste can be used in the treatment of effluents containing dyes. A chemical activation process (NaOH) followed by a magnetization step was evaluated. The effect of three different pyrolysis temperatures of (500 °C, 600 °C, 700 °C) was evaluated. The obtained materials were applied to the adsorption of methylene blue dye. Several kinetic models (pseudo-first order, pseudo-second order, Elovich) and adsorption isotherms (Langmuir, Freundlich, Temkin and Redlich-Peterson) were evaluated. The materials were characterized by thermogravimetric analysis (TGA), Zero Charge Point (PCZ), nitrogen physisorption isotherms and Fourier Transform Infrared (FTIR). For comparison, commercial granular activated carbon was used. The characterization results of the seeds showed that they have high value of cellulose and organic materials being an excellent precursor for synthesis of adsorbent agents. The samples of Activated Carbon synthesized at 500°C (AC 500) and Magnetic Activated Carbon synthesized at 500°C (MAC 500) showed satisfactory results of dye removal when compared to commercially available activated carbon (CAC). The PCZ of the adsorbents showed that the adsorbents have acidic character, as the pyrolysis temperature increased the adsorbent acquired more basic character. The adsorbents have microporous surface and as the pyrolysis temperature increased, the specific surface area decreased. The adsorption kinetics revealed a physiosorption and particle diffusion behavior for the adsorbents and methylene blue. The isotherms revealed that the adsorbents showed favorable adsorption with Langmuir model behavior. The seeds were successfully transformed into activated carbon revealing a potential for industrial application with a performance very similar to the carbon that is available on the market. Although magnetization changed the surface characteristics considerably, the adsorption behavior did not change significantly. Thus, the present work estimated the potential for application of passion fruit seeds in the treatment of textile effluents.